PENGARUH PENDAPATAN BAGI HASIL DEPOSITO MUDHARABAH TERHADAP PROFITABILITAS PADA PT. BPRS BARAKAH NAWAITUL IKHLAS SOLOK - Eli za (Jurnal Menara Ekonomi : Penelitian dan Kajian Ilmiah Bidang Ekonomi, 2017)
Background of question to know what income deposit mudharabah givesignificant effect to profitability of PT. BPRS Barakah Nawaitul Ikhlas Solok. Directionof research to know how many effect income deposit mudharabah give significant effectto profitability in PT BPRS Barakah Nawaitul Ikhlas Solok. Approach of research beused method of quantitative research that explain the indicate was done in PT. BPRSBarakah Nawaitul Ikhlas Solok. Technique of collect the data with observation,interview and documentation. Process the qualitative data used SPSS V.23 Program(Statistical Programming Social Science). Result of this research based on result of testthat be used by SPSS V.23 program. There fore author conculusioned that value ofindependent variable have significant effect to dependent variable of PT. BPRS BarakahNawaitul Ikhlas Solok, that prove H0 refused, with value of significant test t statistic was0.00a, and this value is smaller from value α 0,05. In the meaning that independentvariable (income result divide deposit of mudharabah have significant effect todependent variable (profitability bank).Keyword: Profitability, Income, Deposit, Rentability